1997
DOI: 10.1038/sj.bjp.0700979
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by extracellular ATP and UTP of the stress‐activated protein kinase cascade in rat renal mesangial cells

Abstract: 1 Extracellular adenosine 5'-triphosphate (ATP) and uridine 5'-triphosphate (UTP) have been shown to activate a nucleotide receptor (P 2U receptor) in rat mesangial cells that mediates phosphoinositide and phosphatidylcholine hydrolysis by phospholipases C and D, respectively. This is followed by an increased activity of the mitogen-activated protein kinase cascade and cell proliferation. Here we show that ATP and UTP potently stimulate the stress-activated protein kinase pathway and phosphorylation of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 56 publications
2
31
1
Order By: Relevance
“…This result suggests that extracellular ATP induces rapid and transient phosphorylation of ERK1/2, consistent with previous studies [12,19,20,23] . However, in contrast to previous studies, we found that stimulation of rat mesangial cells with ATP for 60 min resulted in decreased p-ERK1/2 levels when compared with the control.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result suggests that extracellular ATP induces rapid and transient phosphorylation of ERK1/2, consistent with previous studies [12,19,20,23] . However, in contrast to previous studies, we found that stimulation of rat mesangial cells with ATP for 60 min resulted in decreased p-ERK1/2 levels when compared with the control.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggested a role for ATP in high glucose-induced ROS generation in rat mesangial cell. The concentration of ATP used here is similar to that previously reported [14,15,18] and similar to that which has been previously shown to induce proliferation and abnormal secretion of TGF-β1 and ECM in mesangial cells [17,19,20] . Studies have shown that the generation of ROS induced by ATP is associated with an increase in intracellular Ca 2+ levels [14,15,18] .…”
Section: Discussionsupporting
confidence: 67%
“…Whether changes in HuR phosphorylation, either by different PKCs or by the MAPK pathway, account for the ATP-induced HuR redistribution in MC is currently being investigated in our laboratory. In this context it is noteworthy that ATP has been shown to activate different PKC isoenzymes (14,15) as well as the three major MAPK cascades (18,30,31).…”
Section: Atp-inducible Complexes Binding To Mmp-9-specific Ares Contamentioning
confidence: 99%
“…The stimulatory effects of ATP on MMP-9 expression could be potently inhibited by the addition of suramin, a potent, although nonselective, antagonist of P2Y 2 purinoceptors. The occupation of P2Y 2 receptors in rat MC can activate different isoforms of protein kinase C (PKC) (15,24) but also different MAPK pathways including the extracellular signal-regulated kinases (18), the stress-activated protein kinase, and p38-MAPK cascade (30,31). Interestingly, several studies have implicated MAPK pathways as well as PKC-dependent signaling cascades in the up-regulation of MMP-9 expression (32-35), mainly via the activation of NF-B and AP-1 transcription factors (6,(33)(34)(35).…”
Section: Atp-inducible Complexes Binding To Mmp-9-specific Ares Contamentioning
confidence: 99%
“…Altered gene expression results from the induction of several redox-sensitive transcription factors (including NFkB, AP-1, and HIF-1) and the oxidation, nitration, and nitrosation of the potential 500 kinases and 200 phosphatases contained in the cells of the human kidney (23,91,176,181,233,234). Oxidative stress downregulates protein tyrosine phosphatases, while upregulating protein tyrosine kinases, including JNK and p42/p44 (ERK-1/ERK-2) mitogen-activated protein kinase (MAPK) pathways (23,123,130,151,290), although nitric oxide-induced activation of soluble guanylate cyclase and generation of cGMP triggers phosphorylation events that may counteract some of these effects.…”
Section: Ros-induced Gene Expression and Fibrosismentioning
confidence: 99%